Edukasi pengenalan golongan obat sebagai upaya pencegahan efek samping obat - Sari, Putri Rovita; Abdullah, Iqbal Wahib; Atmajaningtyas, Agatha Tyva Julian (JOURNAL of Public Health Concerns, 2026)
Background: Self-medication is still widespread among the public, but often lacks adequate understanding of safety aspects. Lack of knowledge regarding drug classes, dosage and usage, indications, contraindications, and expiration dates potentially increases the risk of side effects. This situation emphasizes the importance of ongoing health education so that the public can use medications appropriately, safely, and according to regulations. Purpose: To increase public knowledge regarding drug classes, including dosage and usage, indications, contraindications, and expiration dates. Method: The community service activity was conducted on December 20, 2025, from 10:00–12:00 WIB in Kedungputri Village, Paron District, Ngawi Regency, East Java. Thirty women aged 30–60 years old were selected using purposive sampling. To evaluate the level of knowledge in this activity, we compared the accumulated answers from respondents before the educational activity (pre-test) and after the educational activity (post-test). Results: The average level of knowledge of respondents regarding drug classification before the pre-test was 41.0% with a standard deviation of 8.32, increasing to 91.7% with a standard deviation of 3.59 after the post-test. Conclusion: The educational activity, which introduced drug classification, dosage, indications, contraindications, and expiration dates, significantly increased respondents' knowledge and understanding of drug use. The interactive community service program proved highly effective in educating respondents about drug classification as a way to prevent side effects. Suggestion: It is hoped that education regarding the proper and correct use of drugs should be continued, involving the health care team and involving all family members. This is important because achieving good health depends not only on the mother's knowledge but also on the understanding and involvement of the entire family in the proper and safe use of drugs. Keywords: Drug classification; Drug side effects; Drug use; Health education Pendahuluan: Penggunaan obat secara mandiri masih marak dilakukan oleh masyarakat, namun sering kali tidak disertai pemahaman yang memadai mengenai aspek keamanan. Minimnya pengetahuan terkait golongan obat, dosis dan cara pakai, indikasi, kontraindikasi, serta tanggal kadaluwarsa berpotensi meningkatkan risiko terjadinya efek samping obat. Kondisi ini menegaskan pentingnya edukasi kesehatan yang berkelanjutan agar masyarakat mampu menggunakan obat secara tepat, aman, dan sesuai aturan. Tujuan: Meningkatkan pengetahuan masyarakat mengenai golongan obat meliputi dosis dan cara pakai, indikasi, kontraindikasi, serta tanggal kadaluwarsa. Metode: Kegiatan pengabdian kepada masyarakat dilaksanakan pada 20 Desember 2025 pukul 10.00–12.00 WIB di Desa Kedungputri, Kecamatan Paron, Kabupaten Ngawi, Jawa Timur. Peserta berjumlah 30 orang ibu-ibu berusia 30–60 tahun yang dipilih secara purposive sampling untuk menjadi responden. Sebagai evaluasi tingkat pengetahuan dalam kegiatan ini dengan membandingkan akumulasi jawaban dari responden sebelum kegiatan edukasi (pre-test) dan setelah kegiatan edukasi (post-test). Hasil: Menunjukkan bahwa rerata tingkat pengetahuan responden dalam kategori baik tentang penggolongan obat sebelum kegiatan edukasi (pre-test) adalah sebesar 41.0% dengan standar deviasi 8.32 meningkat menjadi sebesar 91.7% dengan standar deviasi 3.59 setelah kegiatan edukasi (post-test). Simpulan: Kegiatan edukasi pengenalan mengenai penggolongan obat, dosis, indikasi, kontraindikasi, serta tanggal kadaluwarsa memberikan peningkatan pengetahuan dan pemahaman yang cukup signifikan terhadap responden dalam menggunakan obat-obatan. Program pengabdian kepada masyarakat berupa penyuluhan interaktif terbukti sangat efektif dalam mengedukasi pengenalan golongan obat sebagai upaya pencegahan efek samping obat. Saran: Diharapkan, edukasi mengenai cara dan tatalaksana penggunaan obat yang baik dan benar perlu dilanjutkan dengan melibatkan tim petugas kesehatan serta diikuti oleh seluruh anggota keluarga. Hal ini penting karena pencapaian derajat kesehatan tidak hanya bergantung pada pengetahuan ibu, tetapi juga pada pemahaman dan keterlibatan seluruh keluarga dalam penggunaan obat yang tepat dan aman.